The Alcatraz‐Strategy: a roadmap to break the connectivity barrier in malignant brain tumours - Matthias Schneider; Anna‐Laura Potthoff; Georg Karpel‐Massler; Patrick Schuss; Markus D. Siegelin; Klaus‐Michael Debatin; Hugues Duffau; Hartmut Vatter; Ulrich Herrlinger; Mike‐Andrew Westhoff (Molecular Oncology)
In recent years, the discovery of functional and communicative cellular tumour networks has led to a new understanding of malignant primary brain tumours. In this review, the authors shed light on the diverse nature of cell‐to‐cell connections in brain tumours and propose an innovative treatment approach to address the detrimental connectivity of these networks. The proposed therapeutic outlook revolves around three main strategies: (a) supramarginal resection removing a substantial portion of the communicating tumour cell front far beyond the gadolinium‐enhancing tumour mass, (b) morphological isolation at the single cell level disrupting structural cell‐to‐cell contacts facilitated by elongated cellular membrane protrusions known as tumour microtubes (TMs), and (c) functional isolation at the single cell level blocking TM‐mediated intercellular cytosolic exchange and inhibiting neuronal excitatory input into the malignant network. We draw an analogy between the proposed therapeutic outlook and the Alcatraz Federal Penitentiary, where inmates faced an impassable sea barrier and experienced both spatial and functional isolation within individual cells. Based on current translational efforts and ongoing clinical trials, we propose the Alcatraz‐Strategy as a promising framework to tackle the harmful effects of cellular brain tumour networks.